Gentiana chazaroi (Gentianaceae), a new western Mexican species - Iltis, Hugh H. (Instituto de Ecología, A.C., 1994)
A new, small-leaved, blue-flowered, slenderly rhizomatous Gentiana of section Pneumonanthe related to the larger-flowered G. ovatiloba Kusn. Is described from La Ciudad, on the crest of the Sierra Madre Occidental, Durango, Mexico.